Magische Acetondämpfe. Issue 7 (17th October 2018) - Jonas, Albert; Rubner, Isabel; Oetken, Marco
Translation abstract: Thermal papers contain a three‐component thermochromic mixture of a pH‐sensitive color‐changing leuco dye and a weak acidic developer dissolved in an aliphatic solid solvent‐matrix. Acetone vapors are able to dissolve the solid phase of the solvent, thus allowing the color reaction by the interaction of leuco dye and developer and the formation of the metastable colored dye‐developer complex. At the same time the thermal paper turns black. Renewed evaporation of acetone on the already blackened thermal paper releases the developer from the dye and enables thus the formation of the colorless form of the dye, which results in local discoloration. Competition between the dye−developer and developer−solvent interactions is the basis of the coloring behavior of such thermochromic mixtures, where this experiment provides a suitable and fascinating introduction to the topic in chemistry classes.